Implementation of a Rural Community Diagnostic Testing Strategy for SARS-CoV-2 in Upstate South Carolina - Plumb, Emily V.; Ham, Rachel E.; Napolitano, Justin M.; King, Kylie L.; Swann, Theodore J.; Kalbaugh, Corey A.; Rennert, Lior; Dean, Delphine (Frontiers in Public Health, 2022)
By developing a partnership amongst a public university lab, local city government officials and community healthcare providers, we established a drive-through COVID-19 testing site aiming to improve access to SARS-CoV-2 testing in rural Upstate South Carolina. We collected information on symptoms and known exposures of individuals seeking testing to determine number of pre- or asymptomatic individuals. We completed 71,102 SARS-CoV-2 tests in the community between December 2020 - December 2021 and reported 91.49% of results within 24 hours. We successfully identified 5,244 positive tests; 73.36% of these tests originated from individuals who did not report symptoms. Finally, we identified high transmission levels during two major surges and compared test positivity rates of the local and regional communities. While both communities reached peak case load and test positivity near the same time, the local community returned to moderate transmission as indicated by positivity 4 weeks before the regional community. Our university lab facilitated easy testing with fast turnaround times, which encouraged voluntary testing and helped identify a large number of non-symptomatic cases. Finding the balance of simplicity, accessibility, and community trust was vital to the success of our widespread community testing program for SARS-CoV-2.